Simultaneous Equations Shakespearean Edition

Behold! If x x and y y are integers that fulfill the following simultaneous equations:

{ 5 x 3 + 3 y 3 = 3 ( x + y ) ( x + 1 ) ( y + 1 ) 1 x 3 + 2 y 3 = 1 \begin{cases}5x^3+3y^3=3(x+y)(x+1)(y+1)-1 \\ x^3+2y^3=1 \end{cases}

Then, ponder and determine all probable values of x x and y y . Express thou response as the summation of union (concatenation) of each solution pair ( x , y ) (x, y) in that order. As an illustration, if thou acquired the solution pairs ( 11 , 53 ) (11, 53) , ( 0 , 5 ) (0, 5) , and ( 2 , 0 ) (2, 0) , thou ought to express thy response as 1153 + 05 + 20 = 1178 1153+05+20=1178 . If such solution pairs are non-existent, present nought ( 0 0 ) as thy response.


The answer is 10.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Kenneth Tan
Jul 16, 2018

Relevant wiki: Fermat's Last Theorem

\[\begin{cases}\begin{array}{} 5x^3+3y^3=3(x+y)(x+1)(y+1)-1 & \qquad(1)\\ x^3+2y^3=1 & \qquad(2)\end{array}\end{cases}\]

We perform the following manipulation: ( 2 ) 2 x 3 + 4 y 3 = 2 3 x 3 + 5 y 3 = x 3 + y 3 + 2 ( 3 ) \begin{aligned} (2)&\implies 2x^3+4y^3=2 \\ &\implies 3x^3+5y^3=x^3+y^3+2\qquad(3) \end{aligned}

( 1 ) + ( 3 ) 8 x 3 + 8 y 3 = x 3 + y 3 + 1 + 3 ( x + y ) ( x + 1 ) ( y + 1 ) = x 3 + y 3 + 1 + 3 ( x + y ) ( x y + x + y + 1 ) = x 3 + y 3 + 3 x y ( x + y ) + 1 + 3 ( x + y ) ( x + y + 1 ) = ( x + y ) 3 + 1 + 3 ( x + y ) ( x + y + 1 ) = ( x + y + 1 ) 3 \begin{aligned} (1)+(3)\implies 8x^3+8y^3&=x^3+y^3+1+3(x+y)(x+1)(y+1) \\ &=x^3+y^3+1+3(x+y)(xy+x+y+1) \\ &=x^3+y^3+3xy(x+y)+1+3(x+y)(x+y+1) \\ &=(x+y)^3+1+3(x+y)(x+y+1) \\ &=(x+y+1)^3 \end{aligned}

8 x 3 + 8 y 3 = ( x + y + 1 ) 3 ( 2 x ) 3 + ( 2 y ) 3 = ( x + y + 1 ) 3 \therefore 8x^3+8y^3=(x+y+1)^3\implies(2x)^3+(2y)^3=(x+y+1)^3

Since x x and y y are integers, by Fermat's Last Theorem (also see Fermat's Last Theorem equivalent statements ), this equation has no non-trivial integer solutions.

Thus, one of 2 x 2x , 2 y 2y or x + y + 1 x+y+1 has to be equal to 0 0 .

Case 1: If 2 x = 0 x = 0 2x=0\implies x=0

Then ( 2 y ) 3 = ( 0 + y + 1 ) 3 2 y = y + 1 y = 1 (2y)^3=(0+y+1)^3\implies 2y=y+1\implies y=1 However, ( x , y ) = ( 0 , 1 ) (x, y)=(0, 1) does not satisfy equation ( 1 ) (1) or ( 2 ) (2) .

Case 2: If 2 y = 0 y = 0 2y=0\implies y=0

Then ( 2 x ) 3 = ( x + 0 + 1 ) 3 2 x = x + 1 x = 1 (2x)^3=(x+0+1)^3\implies 2x=x+1\implies x=1 Upon checking, ( x , y ) = ( 1 , 0 ) (x, y)=(1, 0) is indeed a solution to both ( 1 ) (1) and ( 2 ) (2) .

Case 3: If x + y + 1 = 0 x+y+1=0

Then ( 2 x ) 3 = ( 2 y ) 3 x = y (2x)^3=-(2y)^3\implies x=-y But then x + y + 1 = x x + 1 = 1 0 x+y+1=x-x+1=1\neq0 . Oh noes! A contradiction to our original assumption!


Therefore, ( x , y ) = ( 1 , 0 ) (x, y)=(1, 0) is the only integer solution.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...